AN INVESTIGATION ON ITZ MICROSTRUCTURE OF THE CONCRETE CONTAINING WASTE VEHICLE TIRE - Emiroğlu, Mehmet; Yıldız, Servet; Keleştemur, Halidun (My University, 2007)
Interfacial transition zone (ITZ) microstructure o[ rubber reinforced concrete has been examined hy using Scanning Electron Microscopy (SEM). The ruhber reinforced concrete has been prepared in the form consisting of various proportions of waste veh ide tires. The effect of the rubber on interfacial transition zone which exists between tire ruhber and cement paste has been investigated. A total of () batches of concretes has been prepared. Each batches consists of six cylinders which makes totally finy four samples of '/>J50x300 111m. Compressive strength, split tensile strength, unit weight tests and SEM analysis were conducted on the prepared samples. In this particular study, bonding characteristic and fracture analysis between rubher tires and cement paste have been investigated. Although adhesion hetween the rubber and cement paste was weak, roughening interface is formed and it constructed a mechanical interlock.
Bildiri - Yayımlanmış
Bildiri - Kongre ve Sempozyum
Keywords: Interfacial transition zOnc(ITZ); Scanning electron microscopy (SEM); Rubber reinforced concrete: